An Analysis of Educational Value in the Novel “Never Let Me Go” by Kazuo Ishiguro - Sella Rhamadani; Wennyta Wennyta; Ridho Praja Dinata (Universitas Batanghari Jambi, 2021)
This research was aimed to analyzed the educational values in the novel entitled “Never Let Me Go” by Kazuo Ishiguro. The educational values that were expected to found were believing and being faithful to god almighty, being noble moral, healthy, knowledge, competence, creativity, independent, becoming democratic citizen and responsible. The researcher use descriptive qualitative approach to analyzed the novel. Specifically, the researcher used content analysis in gathering the data. The data were gathered by reading the novel thoroughly to identify and classify the educational value that can be found. The results of the study show that there were only seven educational values that can be found in the novel. Sorted from the most frequent encounters to the least are the value of responsibility, creativity, being noble morals, competence, healthy, knowledge and independent. Meanwhile, the other educational values, namely being faithful to god almighty and becoming democratic citizen, were not exist in this novel.Key Words: Novel, Educational Value